A corpus driven analysis of representations around the word ‘ekonomi’ in Malaysian Hansard Corpus - Nor Fariza Mohd Nor,; Anis Anis Nadiah Che Abdul Rahman,; Azhar Jaluddin,; Imran Ho Abdullah,; Sabrina Tiun, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Politicians constantly talk about wealth, power and education, which is often justified on the grounds that it will aid economic growth, which in turn will raise living standard. Thus, many economic issues are seen through the eyes of political beliefs. This paper reports on a corpusdriven analysis around the word ekonomi (economy) in the Malaysian Hansard Corpus. The objectives are to analyse the trend concerning the word ekonomi and to find out the representations around the word ekonom. The analysis showed that the word ekonomi was at its peak in Parliament 6 and Parliament 9, but declined in Parliament 8. The analysis also involved examining the collocational meaning of the word ekonomi and its collocates to determine the categories in which the word ekonomi (economy) was referenced. Positive noun collocates such as pertumbuhan (growth) and kekukuhan (stable) are mainly categorised into the government's policy, government's plan and economic activities in the country. Whilst negative noun collocates such as kemerosotan'(decline) and kelembapan (sluggish) are mostly categorised into economic situation in the country and globally and the government’s effort to handle sluggish economy in Malaysia. The findings also revealed binary conceptualisations of ‘us’ vs. ‘them’, which is common in political discourse. The binary conceptualizations demonstrated that the government’s efforts are commended. On the other hand, the unfavourable economic situation which happened in the country was due to factors which are beyond the government’s control. The paper concludes that the representations around the word ekonomi involved justifying or legitimizing government's course of action. The study suggests a comparison of Hansard data from other Asean or Asian countries, focusing on representation of the word ‘ekonomi’.